Studying the culture of digital society: traditions and new approaches - Saltanovich Irуna P. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
In the context of globalisation and the virtualisation of social communications necessary the formation of new vectors of development of culture, accompanied by changes in human paradigms in the world. Modern collisions undergoing by society and arising as a result of virtualisation and digitalisation of almost all spheres of its life, as well as the fact that the nature of the information man (homo informaticus) is now ambivalent, determined the need to differentiate sociological approaches to studying the place of culture in virtual space, taking into account futurological models of the network society.